Hybrid Power Filter Based on a Six-Switch Two-Leg Inverter - Limongi, Leonardo R.; Genú, Luiz G. B.; Filho, Luís R. Silva; Bradaschia, Fabrício; Azevedo, Gustavo M. S. (Eletrônica de Potência, 2014)
Hybrid power filters (HPFs) are considered an attractive solution to overcome the problem of current harmonics generated by nonlinear loads. They mix low power rating active filters with passive filters, but many of these HPF topologies have a great number of passive components and/or transformers. Based on this fact, new concepts of HPFs, consisting of small rated inverters and LC filters, have been introduced with wide acceptance. The advantage comes from the fact that these HPFs are connected to the grid without any matching transformer. This paper proposes a transformerless HPF based on a new six-switch two-leg inverter with an enhanced harmonic compensation capability. Besides presenting a reduced number of switches when compared with dual topologies, the proposed solution is capable of providing good compensation even for loads with a high harmonic content. Experimental results are presented for a HPF inverter prototype in order to demonstrate the effectiveness of the proposed topology.